INTELLECTUAL PROPERTY LAW IN INDONESIA AFTER 2001 - Valerie Selvie Sinaga (Fakultas Hukum Universitas Gadjah Mada, 2013)
This paper reviews the major changes of intellectual property condition in Indonesia after 2001. In that year, Indonesia, which has become a member of the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) since 1994, was ready to meet its commitment under TRIPS. To do so, Indonesiahas made changes in the areas of legislation, administration, court proceedings, and law enforcement. The paper also discusses problematic issues surrounded the implementation of such changes in Indonesia. Tulisan ini melihat kembali perubahan-perubahan besar dalam bidang hak kekayaan intelektual di Indonesia setelah tahun 2001. Pada tahun tersebut, Indonesia, yang telah menjadi anggota Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) sejak 1994, siap untuk memenuhi komitmennya dalam TRIPS. Untuk memenuhi komitmen tersebut, Indonesia telah membuat perubahan-perubahan dalam bidang legislatif, administratif, tata cara pengadilan dan penegakan hukum. Tulisan ini juga membahas permasalahan di seputar pelaksanaan perubahan-perubahan tersebut.